Multiple Interventions for Diabetic Foot Ulcer Treatment Trial (MIDFUT): study protocol for a randomised controlled trial. Issue 4 (19th April 2020) - Brown, Sarah; Nixon, Jane; Ransom, Myka; Gilberts, Rachael; Dewhirst, Nikki; McGinnis, Elizabeth; Longo, Roberta; Game, Frances; Bojke, Chris; Chadwick, Paul; Chandrasekar, Akila; Chetter, Ian; et al.
Abstract : Introduction: Diabetes affects more than 425 million people worldwide with a lifetime risk of diabetic foot ulcer (DFU) of up to 25%. Management includes wound debridement, wound dressings, offloading, treatment of infection and ischaemia, optimising glycaemic control; use of advanced adjuvant therapies is limited by high cost and lack of robust evidence. Methods and analysis: A multicentre, seamless phase II/III, open, parallel group, multi-arm multi-stage randomised controlled trial in patients with a hard-to-heal DFU, with blinded outcome assessment. A maximum of 447 participants will be randomised (245 participants in phase II and 202 participants in phase III). The phase II primary objective will determine the efficacy of treatment strategies including hydrosurgical debridement ± decellularised dermal allograft, or the combination with negative pressure wound therapy, as an adjunct to treatment as usual (TAU), compared with TAU alone, with patients randomised in a 1:1:1:2 allocation. The outcome is achieving at least 50% reduction in index ulcer area at 4 weeks post randomisation. The phase III primary objective will determine whether one treatment strategy, continued from phase II, reduces time to healing of the index ulcer compared with TAU alone, with participants randomised in a 1:1 allocation. Secondary objectives will compare healing status of the index ulcer, infection rate, reulceration, quality of life, cost-effectiveness and incidence of adverse events over 52 weeks post randomisation. Phase II and phase III primary endpoint analysis will be conducted using a mixed-effects logistic regression model and Cox proportional hazards regression, respectively. A within-trial economic evaluation will be undertaken; the primary economic analysis will be a cost-utility analysis presenting ICERs for each treatment strategy in rank order of effectiveness, with effects expressed as quality-adjusted life years. The trial has predefined progression criteria for the selection of one treatment strategy into phase III based on efficacy, safety and costs at 4 weeks. Ethics and dissemination: Ethics approval has been granted by the National Research Ethics Service (NRES) Committee Yorkshire and The Humber - Bradford Leeds Research Ethics Committee; approved 26 April 2017; (REC reference: 17/YH/0055). There is planned publication of a monograph in National Institute for Health Research journals and main trial results and associated papers in high-impact peer-reviewed journals. Trial registration number: ISRCTN64926597 ; registered on 6 June 2017